REKOSNTRUKSI JARINGAN ENDOKARST DAN ANALISIS DEBIT SERTA KIMIA AIRTANAH KAWASAN KARST DAERAH BUNIAYU, KABUPATEN SUKABUMI, JAWA BARAT - Priyono, Imam
Karst morphological phenomenon which is interesting in Buniayu karst Area, Sub Province Sukabumi, West Java is an example of the formation of fracture and under surface cavities in the form of caves, cave network and also disappearing surface drainage into karst aquifer. This phenomenon is the background for this hydrogeological research study is about reconstruction of endokarst network, discharge analysis and chemical groundwater parameter, also to know the aquifer system and groundwater flow. The research area is located in the Buniayu karst area, Regency Sukabumi, West Java. It is about 20 km south of Sukabumi, West Java and covers about 20 km2 area. The research area has three kinds of aquifer, namely karst aquifer, weathered breccia aquifer and weathered sandy clay aquifer. The focus of this research is at karst aquifer having 15 springs and 2 underground river (Cipicung Cave dan Siluman Cave). The karst spring, i.e. the Bibijilan spring has a maximum discharge of 1071 l/second, whereas the other 14 spring have various discharge between 2 – 60 l/second. For endokarst network reconstruction, the research is done by mapping step and compass method along the cave, and resistivity study with 8 lines using Wenner- Schlumberger and Misse A’la Mase method while the interpretation of calibration study is from laboratory test result using those two geophysics methods. The result using Wenner-Schlumberger method with the interpretation using laboratory test result, is indicated with cave position and cave diameter, namely : Line-1 (775 mapl, no detection of cavities), Line-2 (776 mapl, no detection of cavities), Line-3 (777 mapl, 20 m x 10 m), Line-4 (775 mapl, 42 m x 15 m), Line-5 (774 mapl, 55 m x 10 m), Line-6 (775 mapl, 25 m x 15 m), Line-7 (774 mapl, 6 m x 3 m), Line-8 (775 mapl, 50 m x 5 m). The result using Misse A’la Mase showed that in the bottom cave Cipicung (total 640 meter, all filled with water), while in Siluman Cave (total 600 meter, stream water only along 100 meter from mouth cave in the southern part). In the other parts it is dry and water flows through little cavities and fracture at the bottom of Siluman Cave. Measurement of spring water discharge is conducted at 20 spring from 15 spring karst aquifer, 3 spring weathered breccia aquifer and 2 spring weathered sandy clay aquifer. Measurement of discharge springs is conducted in 7 months (June – December iv 2005). Based on the measurement result from 20 springs, it shows that the smallest discharge is 0,1 l/second in sandy clay aquifer at Pasir Salam area. In karst aquifer, the maximum discharge is 1071 l/second (Spring GP-6) in aquifer karst limestone at Bibijilan area and other springs vary from 2 – 60 l/detik. The result shows that aquifer karst limestone represent productive aquifer. Variation of spring discharge in karst aquifer is very much influenced by change of season which, this can be shown by maximum fluctuation of spring discharge in Bibijilan (discharge 1011/detik) to rainy season (discharge 1071 l/detik). The behaviour of discharge in aquifer karst have special characteristic, where change of season having an effect to discharge fluctuation which mounting very keen (maximal increase 60 l/second from dry season to rainy season). Measurement for physical parameter groundwater (temperature of air-water), pH, DHL (Conductivity electric) is conducted to 20 spring sample and 7 underground river in December 2005. Chemical analysis of groundwater (main element) is conducted 8 sample taken from 3 springs, 3 underground river, 1 well dan 1 rain water. Water sample is taken at 2 periods, in June 2005 (dry season) dan January 2006 (rainy season). Physical water analysis is conducted to 20 sample springs and 7 sample underground river water. The data result is as follows : a) pH gyration (5 – 7,5) which indicating that the nature of water in research area is relatively acid – to normal; b) DHL gyration (18 – 364 ?S), where the smallest DHL value (18 – 26 ?S) is at weathered sandy clay aquifer. This is an indication the time contact between water and sandy clay is not long. The biggest DHL (364 ?S) value is found at aquifer karst limestone. This also indicating that the time contact water and limestone is relatively long; a) Temperature zonation for karst aquifer is found in Hypothermal zonation, while temperature zonation for example of underground river water in mesothermal zonation. According to Piper diagram’s, the result is a) Calcium Bicarbonate facies at aquifer karst limestone water (from spring and underground river water); b) Natrium, Calcium, Magnesium Bicarbonate facies at aquifer sandy clay. The chemical composition of ground water is related to the rock chemical compocition, this can be seen from result of petrographic analysis with support the result of chemical analysis composition of groundwater, the result is calcite mineral (CaCO3) and clay mineral. v Based on geometrical analysis of spring at Bibijilan at aquifer karst Buniayu. It is interpreted that the groundwater system in karst aquifer are input and output local places through karst aquifer which can be characterized by limestone emsisting of fracture with 15 fracture intensity/m2, open fracture various from 10 – 62 cm long. This is indicated by a) water temperature (T=22oC) is still close to air temperature (T=25oC), b) concentration bicarbonate cation (HCO3 -) is 204,5 mg/l or 3,352 meq/l and DHL value 364 ?S. Besides that discharge fluctuation is very influenced by rainy season with an increase of 20 l/second during 1 month after rain, while discharge will be low 2 month after no rain fall. Strive conservation for Bibijilan spring, especially discharge water is for instance to take care of recharge area which is located in karst area it self, but it is still necessary to do delineation in the discharge area more accurately.